Contribution of KRAS mutations and c.2369C > T (p.T790M) EGFR to acquired resistance to EGFR-TKIs in EGFR mutant NSCLC: a study on circulating tumor DNA - Del Re, Marzia (Oncotarget, 2016)
INTRODUCTION: KRAS oncogene mutations ((MUT)KRAS) drive resistance to EGFR inhibition by providing alternative signaling as demonstrated in colo-rectal cancer. In non-small cell lung cancer (NSCLC), the efficacy of treatment with EGFR tyrosine kinase inhibitors (EGFR-TKIs) depends on activating EGFR mutations ((MUT)EGFR). However, inhibition of EGFR may select resistant cells displaying alternative signaling, i.e., KRAS, or restoration of EGFR activity due to additional (MUT)EGFR, i.e., the c.2369C > T ((p.T790M)EGFR). AIM: The aim of this study was to investigate the appearance of (MUT)KRAS during EGFR-TKI treatment and their contribution to drug resistance. METHODS: This study used cell-free circulating tumor DNA (cftDNA) to evaluate the appearance of codon 12 (MUT)KRAS and (p.T790M)EGFR mutations in 33 advanced NSCLC patients progressing after an EGFR-TKI. RESULTS: (p.T790M)EGFR was detected in 11 (33.3%) patients, (MUT)KRAS at codon 12 in 3 (9.1%) while both (p.T790M)EGFR and (MUT)KRAS codon 12 were found in 13 (39.4%) patients. Six patients (18.2%) were KRAS wild-type ((WT)KRAS) and negative for (p.T790M)EGFR. In 8 subjects paired tumor re-biopsy/plasma samples were available; the percent concordance of tissue/plasma was 62.5% for (p.T790M)EGFR and 37.5% for (MUT)KRAS. The analysis of time to progression (TTP) and overall survival (OS) in (WT)KRAS vs. (MUT)KRAS were not statistically different, even if there was a better survival with (WT)KRAS vs. (MUT)KRAS, i.e., TTP 14.4 vs. 11.4 months (p = 0.97) and OS 40.2 vs. 35.0 months (p = 0.56), respectively. CONCLUSIONS: (MUT)KRAS could be an additional mechanism of escape from EGFR-TKI inhibition and cftDNA is a feasible approach to monitor the molecular development of drug resistance.